Non-targeted metabolomics reveals the effects of fermented methods on the flavor, quality, and metabolites of whipping cream - Xin Zhou; Jian-Guo Zhang; Fei Hu; Zhi-Jing Ni; Kiran Thakur; Zhao-Jun Wei (Food Chemistry: X)
Flavored fermented whipping cream has received particular attention. However, the effects of different fermentation methods on the quality and flavor of whipping cream remain elusive. This study characterized the flavor, quality, and metabolites of whipping cream produced by different fermentation methods based on non-targeted metabolomics. The results showed that the quality, color, and flavor of fermented whipping cream were significantly improved. Notably, the GMF fermentation group had the highest variety and content of flavoring substances. A total of 729 shared metabolites were identified, mainly including glycerophospholipids (151, 20.71 %), fatty acyls (114, 15.64 %), organoacyls (89, 12.21 %). Whipping cream by the mixed bacteria fermentation contained lower lipids and higher flavor amino acids, while the contents of bitter peptides and some organic acids and their derivatives were significantly lower. The results of this study provide a valuable reference for enhancing the quality, flavor, flavor of whipping cream using mixed bacteria fermentation methods.